Shoot Heterogeneity Effects on Shiraz/Richter 99 Grapevines. III. Leaf Chlorophyll Content - Cloete, H.; Archer, E.; Novello, V.; Hunter, J.J. (South African Journal of Enology and Viticulture, 2016)
In this study, the leaf chlorophyll content of normally developed and underdeveloped shoots was compared in an attempt to quantify the effect of shoot heterogeneity in a Shiraz/Richter 99 vineyard, located in the Stellenbosch area of the Western Cape, South Africa. Comparisons are also made between normally developed and underdeveloped shoots from shaded and well-exposed canopies. No positive correlation was found between the photosynthetic activity and the chlorophyll concentration of the leaves at five weeks after véraison. Equal amounts of chlorophyll per cm2 and a non-significant difference in the assimilation rate were calculated for the leaves of normally developed and underdeveloped shoots. No significant differences were found between the shaded and well-exposed canopies. It therefore appears that it is the effective surface area per leaf or per shoot rather than the chlorophyll concentration or activity that may be responsible for any apparent difference in the photosynthetic output of the leaves from normally developed and underdeveloped shoots in shaded or well-exposed canopies.